On Deriving Statecharts Supervision Models from SDL Specifications Using SSM - Silva Filho, Antonio Mendes da (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24438, 1996)
This paper presents a discussion of using software supervision as a means of improving the software reliability of reactive systems during the in-use phase. Supervision software consists of monitoring both the inputs and outputs of a target system and checking them against the target system's specification. All discrepancies between observed sequences of signals and the target system's specification are reported as failures. The emphasis of this paper is on showing the suitability of using Statecharts as a formal technique to specify the reactive system supervisor. The target reactive system is assumed to be specified in SDL (Specification and Description Language). Statecharts-based Supervisor Modeling (SSM) is presented by using examples. As well, benefits of this approach are discussed.